Statistical analysis of EMIC waves in plasmaspheric plumes from Cluster observations. Issue 8 (9th August 2013) - Usanova, M. E.; Darrouzet, F.; Mann, I. R.; Bortnik, J.
Abstract: [1] Recently, electromagnetic ion cyclotron (EMIC) wave generation in plasmaspheric plumes has been the subject of extensive discussion. Theory predicts that regions of detached cold, dense plasma immersed in relatively low background magnetic field should aid EMIC wave growth and may provide conditions for interaction between the EMIC waves and relativistic (MeV) electrons, leading to energetic particle loss into the atmosphere. Since plasmaspheric plumes are specific to disturbed geomagnetic conditions, the link between EMIC waves and plumes may be especially important for radiation belt dynamics during magnetic storms. In this work, we present an in situ survey of EMIC waves in plasmaspheric plumes using data from the Cluster satellites and will address the question of whether plumes are important for EMIC wave generation from a statistical perspective. We used a survey of plasmaspheric plumes between 2001 and 2006 identified from the Waves of High frequency and Sounder for Probing of Electron density by Relaxation (WHISPER) sounder measurements. We further identified EMIC waves from simultaneous (with WHISPER) magnetic field measurements by the fluxgate magnetometer instruments and investigated the relationship between these two data sets. Only 10% of the time when Cluster‐observed plumes along its orbit did we also observe EMIC waves. The wave occurrence outside plumes is further significantly reduced and is ~20 times lower in immediately adjacent regions than inside plumes. We found that cold plasma density was not a good predictor of EMIC occurrence inside the plumes and that the absolute density does not affect the EMIC probability. On the other hand, enhanced solar wind dynamic pressure significantly increases EMIC wave occurrence rate inside the plumes. Key Points: We analyzed 6 years of the Cluster satellite data EMIC waves were seen during 10% of the time when Cluster observed plumes Enhanced solar wind pressure controls EMIC occurrence in plumes